Relation between shape and the phenomenon of flutter for bridge deck-like bluff bodies - Nowicki, T.; Flaga, A. (Archives of Mechanics, 2011)
The paper deals with experimental analysis of the influence of cross–section shape of a body on the phenomenon of flutter. The aeroelastic section model that was the object of study in a laboratory corresponded to a central section of a long bridge deck. Such structures are subjected to flutter like aeroplane wings or helicopter rotors. Unlike in aviation, bridge decks cross-sections can be designed much more freely. The analysis is concentrated on a problem how the cross-section shape of a deck can affect interaction with incoming air stream. The results obtained suggest that the influence is closely related to elastic characteristics of a deck.